2014
DOI: 10.1177/2040622313513313
|View full text |Cite
|
Sign up to set email alerts
|

The role of bariatric surgery in the treatment of diabetes

Abstract: Abstract:The obesity epidemic contributes to approximately 44% of the world's type 2 diabetes burden. Bariatric surgery is an effective treatment for type 2 diabetes mellitus in patients with morbid obesity as it improves glycaemia, blood pressure, lipids and inflammation. This review describes the evidence supporting the addition of bariatric surgery to the treatment algorithms used by diabetologists. We emphasize the need to view bariatric surgery as an adjuvant therapy which should not be used instead of bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 74 publications
1
17
0
Order By: Relevance
“…Food intake is reduced following bariatric surgery as a consequence of either reducing the size of stomach through insertion of a gastric band, or the removal of a part of the stomach or reducing the length of the small intestine. Long-term studies indicate this type of surgery, is not effective for weight loss [5], but also ameliorate a variety of obesity-related diseases such as DM and CVD [8]. However, some adverse effects may be expected due to the magnitude of the procedure [9].…”
Section: Introductionmentioning
confidence: 99%
“…Food intake is reduced following bariatric surgery as a consequence of either reducing the size of stomach through insertion of a gastric band, or the removal of a part of the stomach or reducing the length of the small intestine. Long-term studies indicate this type of surgery, is not effective for weight loss [5], but also ameliorate a variety of obesity-related diseases such as DM and CVD [8]. However, some adverse effects may be expected due to the magnitude of the procedure [9].…”
Section: Introductionmentioning
confidence: 99%
“…Bariatric surgery can lead to significant improvement of type 2 diabetes mellitus (T2DM) in morbidly obese patients [ 1 , 2 ]. A meta-analysis by Buchwald et al [ 3 ] has shown that laparoscopic adjustable gastric banding (LAGB) and biliopancreatic diversion (BPD) induces remission of T2DM in 50% and up to 95% of bariatric T2DM patients, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…T2DM rate increases alongside with increment of obesity over the world. An estimate of 170 million people affected by T2DM worldwide was recently reported [5]. The first treatment of T2DM is surely lifestyle modification alongside with pharmacotherapy.…”
Section: Introductionmentioning
confidence: 99%